Business Information Technology Models for Women Farmer Group in Indonesia - Soehardjoepri; Muslichah Erma Widiana; Mahmudah Enny Widyaningrum (Universitas Muhammadiyah Sidoarjo, 2021)
The existence of women farmer groups in the use of land for agriculture, such as existing fruit and vegetables, deserves a response to the follow-up, considering that the activities of women farmer groups have great potential. However, the professions as farmers and agricultural laborers, the income of female farmers and agricultural laborers does not necessarily depend on the season. With the ability to manage further processed agricultural products, they can have reliable income and use a marketing system that is adjusted to the times. This research is a model trial with the title